The Ostmarkgesetz of 14 April 1939 – One of the Normative Grounds of the Annexation Of Austria - Nieścior, Bartosz (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2021)
The article presents the political and legal changes that accompanied the passing and then the introduction of the Ostmarkgesetz in Austria in 1939. It also contains a detailed analysis of the structure and layout of this normative act. The Ostmarkgesetz was extremely important because it thoroughly changed the administrative organization and introduced a new administration of the state in this area. The consequences had a significant impact on the Austrian legal order. This law is considered to be one of the main tools of the direct annexation of Austria by the Third Reich. This was the beginning of the subsequent war conquests of the Nazi state.